The Influence of Soft Skills and Adversity Quotient on Work Readiness of Students in the Faculty of Economics at Muhammadiyah University Makassar - Nasrullah , Nasrullah; Mariana, Lina; Nur Sandi Marsuni; Surya Dharma (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Indonesia's optimism to become one of the top 10 world economic powers by 2030. With this target, it is necessary to increase human resources who are ready and globally competitive, especially in higher education institutions. These institutions are expected to produce graduates who are ready for the workforce. However, based on interviews conducted with students of the Faculty of Economics, University of Muhammadiyah Makassar, it has been found that students in the final stages of their studies generally lack optimal preparation for their personal experiences. This is evident from their limited involvement in organizational activities and entrepreneurial ventures. Even when asked about their plans after completing their studies, many students expressed uncertainty and claimed that they were unaware of their future direction. Work readiness must be fostered and developed as early as possible by students to be ready for a career in the future. This research was conducted at the Faculty of Economics, University of Muhammadiyah Makassar. The population in this study was all students at the Faculty of Economics, University of Muhammadiyah Makassar amounted to 5045 from 5 study programs, To obtain a representative sample, sampling was carried out with proportional random sampling techniques with a sample of 371 students. The results showed that: 1) there is a positive influence of soft skills on the job readiness of students of the Faculty of Economics, University of Muhammadiyah Makassar, 2) there is a positive influence of adversity quotient on the job readiness of students of the Faculty of Economics, University of Muhammadiyah Makassar, 3) the influence of soft skills and adversity quotient simultaneously on the job readiness of students of the Faculty of Economics, University of Muhammadiyah Makassar, the magnitude of the influence imultant is 11%.